Leptomeningeal cyst in an adult following childhood trauma: a case report - Bereket Girum Beyene, MD; Suleyman Fantahun Endris, MD; Michael Teklehaimanot Abera, MD; Rebil Heiru Jemal, MD; Abdi Alemayehu Dhuguma, MD (Radiology Case Reports)
Leptomeningeal cyst, also known as growing skull fracture in adults, is a very rare complication usually related to childhood head trauma. It is presumed to occur following a skull fracture during childhood associated with a Dural tear and projection of arachnoid membranes, which gradually erodes the fractured bone and grows aided by the normal pulsations of the brain. Here, we present a case of Type 1 leptomeningeal cyst in the left parietal bone in a 22-year-old male adult who presented years after sustaining head injury during his early childhood. Computed tomography scan was crucial in the accurate diagnosis of the case.